2018
DOI: 10.1002/adhm.201701506
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoplate‐Enhanced Chemiluminescence and Macromolecular Shielding for Rapid Microbial Diagnostics

Abstract: With the global rise of antimicrobial resistance, rapid screening and identification of low concentrations of microorganisms in less than 1 h becomes an urgent technological need for evidence-based antibiotic therapy. Although many commercially available techniques are labeled for rapid microbial detection, they often require 24-48 h of cell enrichment to reach detectable levels. Here, it is shown that the widely used reducing agent tris(2-carboxyethyl)phosphine (TCEP) can also act as a powerful oxidant on gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Chemiluminescence (CL) is a practical opto-chemical approach for designing real-life sensing applications, e.g., safety control within food and pharmaceutical industries, environmental hazardous contaminants monitoring and clinical examination, using the discharged radiation for high sensitivity analysis of the target molecule [13][14][15][16][17][18]. The addition of superparamagnetism characteristics onto CL bioassays in means of magnetic nanoparticles (MNPs), alleviate the high-throughput immunoassay protocols by convenient separation, widespread the linear sensing range, enhance the reaction kinetics and encompass high surface area for collected biomolecular recognition [19].…”
mentioning
confidence: 99%
“…Chemiluminescence (CL) is a practical opto-chemical approach for designing real-life sensing applications, e.g., safety control within food and pharmaceutical industries, environmental hazardous contaminants monitoring and clinical examination, using the discharged radiation for high sensitivity analysis of the target molecule [13][14][15][16][17][18]. The addition of superparamagnetism characteristics onto CL bioassays in means of magnetic nanoparticles (MNPs), alleviate the high-throughput immunoassay protocols by convenient separation, widespread the linear sensing range, enhance the reaction kinetics and encompass high surface area for collected biomolecular recognition [19].…”
mentioning
confidence: 99%
“…Chemiluminescence (CL) is widely applied chemically driven electromagnetic radiation for real-life applications, from clinical monitoring, food and pharmaceutical safety control, and up to trace levels of environmental pollutants analysis, utilizing its high sensitivity toward the assessment of the limiting target reactant involved in the luminol reaction [1,2,3,4,5,6,7,8,9,10,11]. The low emitted radiation within complex samples such as blood, milk, urine, or biological tissues, can be efficiently augmented by the addition of a catalyst, e.g., metal or semiconductor nanoparticles, catalytic ions, enzymes, into the luminol CL system.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (GNPs) are one of the most frequently used nanoparticles for analytical applications harnessing the ease of opto-electronic property fine-tuning by mild changes in the nanoparticles size, morphology, surface functionality, and local environment [12,13]. Indeed, numerous case studies and reports employed GNPs for enhanced CL (eCL) presenting a repertoire of novel ultrasensitive bioassays [4,5,6,12,13,14,15,16,17,18,19]. Singh et al have reported the use of sequence-specific single-stranded DNA probes anchored on the exterior of GNPs surface for the hybridization with the complementary DNA target regions of Ceratocystis fagacearum [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, chemiluminescence (CL) relies on illumination produced by chemical reactions of trace analysts, which can be exempted from the excitation light source and therefore avoid interference from light scattering . As a result, CL possesses simple instrumentation and operation, wide calibration ranges, and suitability for miniaturization, , offering a great potential for the determination of pathogenic microorganisms . Classically, luminol-based CL reaction coupling of hydrogen peroxide (H 2 O 2 ) and other oxidations is the main illuminated medium because of its inexpensiveness and high sensibility.…”
mentioning
confidence: 99%